Acute Kidney Injury Outcomes of Elderly and Nonelderly Patients in the Medical Intensive Care Unit of a University Hospital in a Developing Country. (30th January 2020) - Pongsittisak, Wanjak; Phonsawang, Kashane; Jaturapisanukul, Solos; Prommool, Surazee; Kurathong, Sathit
Abstract : Background . Aging is associated with a high risk of acute kidney injury (AKI), and the elderly with AKI show a higher mortality rate than those without AKI. In this study, we compared AKI outcomes between elderly and nonelderly patients in a university hospital in a developing country. Materials and Methods . This retrospective cohort study included patients with AKI who were admitted to the medical intensive care unit (ICU) between January 1, 2012, and December 31, 2017. The patients were divided into the elderly (eAKI; age ≥65 years; n  = 158) and nonelderly (nAKI; n  = 142) groups. Baseline characteristics, comorbidities, principle diagnosis, renal replacement therapy (RRT) requirement, hospital course, and in-hospital mortality were recorded. The primary outcome was in-hospital mortality. Results . The eAKI group included more females, patients with higher Acute Physiology and Chronic Health Evaluation II scores, and patients with more comorbidities than the nAKI group. The etiology and staging of AKI were similar between the two groups. There were no significant differences in in-hospital mortality (p = 0.338 ) and RRT requirement (p = 0.802 ) between the two groups. After adjusting for covariates, the 28-day mortality rate was similar between the two groups (p = 0.654 ), but the 28-day RRT requirement was higher in the eAKI group than in the nAKI group (p = 0.042 ). Conclusion . Elderly and nonelderly ICU patients showed similar survival outcomes of AKI, although the elderly were at a higher risk of requiring RRT.